Cusatuzumab for treatment of CD70‐positive relapsed or refractory cutaneous T‐cell lymphoma. Issue 5 (2nd November 2021) - Leupin, Nicolas; Zinzani, Pier Luigi; Morschhauser, Franck; Dalle, Stéphane; Maerevoet, Marie; Michot, Jean‐Marie; Ribrag, Vincent; Offner, Fritz; Beylot‐Barry, Marie; Moins‐Teisserenc, Hélène; Zwaenepoel, Karen; de Winne, Koen; et al.
Abstract : Background: The clinical benefit of cusatuzumab, a CD70‐directed monoclonal antibody with enhanced effector functions, was investigated in patients with relapsed/refractory (R/R) cutaneous T‐cell lymphoma (CTCL). Methods: In this cohort expansion of the ARGX‐110‐1201 study, 27 patients with R/R CTCL received cusatuzumab at 1 (n = 11) or 5 mg/kg (n = 16) once every 3 weeks to investigate its safety, dose, and exploratory efficacy. The pharmacokinetics, immunogenicity, CD70 expression, and CD70/CD27 biology were also assessed. Results: The most common adverse events included infusion‐related reactions, pyrexia, and asthenia. Eighteen serious adverse events (grade 1‐3) were reported in 11 patients; 1 of these (vasculitis) was considered drug‐related. For 8 of the 11 patients receiving 1 mg/kg, anti‐drug antibodies (ADAs) affected the minimal concentration, and this resulted in undetectable cusatuzumab concentrations at the end of treatment and, in some cases, a loss of response. This effect was greatly reduced in the patients receiving 5 mg/kg. The overall response rate was 23%; this included 1 complete response and 5 partial responses (PRs) in 26 of the 27 evaluable patients. In addition, 9 patients achieved stable disease. The mean duration on cusatuzumab was 5.2 months, and the median duration was 2.5 months. Patients with Sézary syndrome (SS) achieved a 60% PR rate with a dosage of 5 mg/kg and a 33% PR rate with a dosage of 1 mg/kg; this resulted in an overall response rate of 50% for patients with SS at both doses. Conclusions: Cusatuzumab was well tolerated, and antitumor activity was observed at both 1 and 5 mg/kg in highly pretreated patients with R/R CTCL. The observed dose‐dependent effect on exposure supports the use of 5 mg/kg for future development. Abstract : Cusatuzumab, a monoclonal antibody targeting CD70, is well tolerated and shows dose‐dependent evidence of antitumor activity in a heavily pretreated patient population with cutaneous T‐cell lymphoma. The overall response rate was 23% with increased efficacy in patients with Sézary syndrome, warranting further clinical development.